Life Cycle and Career Cycle in Socialist Bulgaria - Wenkart Smollett, Eleanor (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1989)
The author examines changes in the interaction between life cycle patterns and career patterns during the period of socialist development in Bulgaria. She explores the implications for the interconnected problems of young people and middle-aged people regarding their roles – productive and reproductive – in the society. The author has made eight research trips to Bulgaria, over an eighteen year period. As background to the analysis, the author reviews the changes in Bulgarian society up to summer, 1989, particularly developments during the socialist period from 1944.